Digital Learning Transformation: Implementing Technology-Based Cultural Discovery Learning to Enhance English Teaching Competence - Rafiqa, Rafiqa; Aswad, Muhammad (STAIN Majene, 2026)
Digital transformation has reshaped English language teacher education by requiring pre-service teachers to develop not only pedagogical knowledge but also digital literacy, intercultural awareness, and reflective teaching competence. However, the integration of technology, culture, and pedagogy remains limited in many teacher education contexts. This study investigated the effectiveness of technology-based Cultural Discovery Learning (CDL) in enhancing the teaching competence of pre-service English teachers and examined the quality of its implementation in the learning process. A quantitative approach with a quasi-experimental design was employed. The participants were 77 undergraduate students from the English Education Study Program at Universitas Sulawesi Barat, consisting of 38 students in the experimental group and 39 students in the control group. Data were collected through pre-tests, post-tests, classroom observation, and documentation. Descriptive statistics and an independent-sample t-test were used to analyze the data. The findings revealed that the experimental group achieved a higher gain score (21.39) than the control group (7.62). The independent-sample t-test showed a significant difference between the two groups, t(75) = 6.212, p < .001. Observation results also indicated that the CDL model was implemented with very high fidelity, with an average score of 90 across cultural objectives, authentic digital media, cultural discovery activities, reflection, and digital product creation. These findings suggest that technology-based CDL is an effective pedagogical framework for developing pre-service English teachers’ pedagogical, digital, intercultural, and reflective competencies.